10.1152/physiolgenomics.00169.2022 (CrossRef Listing of Deleted DOIs, 2000)
Sexual and gender minority (SGM) adults, as well as Black, Indigenous, and People of Color (BIPOC), face inequities regarding cardiovascular disease (CVD) risk in the United States compared to their heterosexual and White counterparts. We previously found that prehealth students experience low baseline knowledge concerning CVD risks among historically marginalized communities and struggle to propose interventional strategies that could reasonably address these disparities. We hypothesize that incorporating public health approaches that address behavior change (e.g., the health belief model) into a pathophysiology lecture enhances students' ability to problem solve regarding health disparity in SGM and BIPOC communities. A single lecture intervention was delivered to 100 students enrolled in a cardiovascular pathophysiology course. Paired pre- and postintervention surveys evaluating both subjective and objective learning outcomes were used to assess the efficacy of our intervention. Twenty-nine students answered the prelecture survey, and twelve students answered our postlecture survey. Students' knowledge of the mechanistic factors contributing to CVD disparities in BIPOC and SGM populations, and their ability to create solutions addressing these disparities, increased after the lecture intervention. Furthermore, the addition of public health intervention frameworks moderately improved students' ability to propose novel intervention strategies in a population-specific manner. Teaching interdisciplinary models of intervention to physiology students may represent a novel approach that enhances their ability to generate approaches to reducing CVD risk in marginalized communities.NEW & NOTEWORTHY The present study finds that teaching methods from public health disciplines in the physiology classroom improve students' understanding of how to develop ideas to reduce cardiovascular disease (CVD) inequities. Our data support the notion that a multidisciplinary approach on the part of the instructor, integrating disciplinary knowledge from outside of physiology, is an effective approach to enhance problem-solving skills regarding CVD in marginalized populations.